Physics and Electrodynamics of High-Frequency Torch Discharge; KORUS 2003; Vol. 3 - Vlasov V. A. Viktor Alekseevich (2003, 2003)
On the basis of amplitude-phase characteristics of high-frequency torch discharge electromagnetic components there has been determined the presence of reflected electromagnetic wave in a discharge channel. A new electrodynamics discharge model has been introduced according to which a discharge channel is considered as a current line of finite length